Fabrication and electrochemical analysis of nanostructured materials for supercapacitors - 이혜민 (The Graduate School, Ajou University, 2015)
Thi s thes is focuses on the fabr icat ion and elect rochemical analys is of nanos t ructured mater ial s for supercapaci tor s . The techniques employed in this work for producing elect rode mater ial s include elect rodepos i t ion and hydrothermal method. Elect rodeposi ton i s capable of producing high qual i ty of nanos t ructured mater ials and leading to a di rect depos i t ion of them on an elect rode. Therefore i t can skip a ser i es of compl icated proces ses such as synthes izing powder s , mixing powder s wi th a conduct ing agent and a binder, and making an elect rode. A hydrothermal method i s al so used to synthes ize the graphene -based metal oxide s . Al though i t needs an inconvenient s tep for fabr icat ing elect rode wi th oxide powder s , i t is wel l known as the mos t effect ive method for producing a large scale of graphene and graphene compos i tes so far. Chapter 1 descr ibed the fundamental s and elect rode mater ial s for supercapaci tor s and thei r recent proces s ing techniques . Based on the working mechani sm, there are two types of supercapaci tor s: ( i ) elect r ic double-layer capaci tor (EDLC) and ( i i ) pseudocapaci tor. The select ion of elect rode mater ial s i s a key factor to determining the per formance of supercapaci tor s . There i s increasing interes t in the development of advanced elect rode mater ial s having relat ively low cos t , large speci f ic sur face area, conduct ivi ty, and easy proces sabi l i ty. Among the mater ial s l i s ted in Chapter 1, manganese oxides have received much at tent ion as an elect rode mater ial for supercapaci tors because of thei r natural abundance and low cos t . However, manganese oxides have l imi tat ions such as low sur face area, poor elect r ical conduct ivi ty, and rel at ively smal l speci f ic capaci tance value. To improve the elect rochemical per formance of manganese oxides for supercapaci tor s , the use of sur factant s , manganese -based binary metal oxides , and graphene-based oxides have been at tempted to increase thei r sur face area and enhance the conduct ivi ty of manganese oxide s . In Chapter 2, the addi t ion of tet radecyl t r imethyammonium bromide (TTAB) as a sur factant was at tempted to enhance the pseudo -capaci t ive proper ty of manganese oxide f i lms . The effect of sur factant concent rat ion on the sur face morphology (cor respondingly, sur face area) of the nanos t ructured manganese oxide was s tudied and elect rochemical proper t ies of the elect rodepos i ted manganese oxide as an supercapaci tor elect rode were al so inves t igat ed. In Chapter 3, the incorporat ion of a t rans i t ion metal into manganese oxides to form binary metal oxides such as manganese -nickel oxide nanocompos i tes wi th cont rol led micro/nanos t ructures was developed to overcome the l imi tat ions of s ingle metal oxide such as poor elect r ical conduct ion, insuff icient elect rochemical cycl ing s tabi l i ty, l imi ted vol tage operat ing window and low speci f ic capaci tance . The manganese oxide and manganese -nickel oxide f i lms were prepared on a graphi te sheet by anodic elect rodepos i t ion. The s t ructural , morphological , and elect rochemical proper t ies of the elect rodepos i ted manganese -nickel oxide f i lms were di scus sed. Combining manganese oxides wi th mater ial s that have high speci f ic sur face areas and conduct ivi t ies is thought to be an at t ract i ve opt ion. Graphene-based metal oxide compos i tes exhibi ted bet ter elect ronic per formance than pure metal oxides because of thei r excel lent supercapaci t ive per formance , which i s suppor ted by the two dimens ional s t ructure of sp2 - hybr idized carbon atoms in graphene sheet s . In Chapter 4, we developed a di rect and envi ronmental ly benign method to prepare Mn3O4 nanopar t icles on graphene via a one-s tep hydrothermal method wi thout the use of s t rong acids and toxic reducing agent s . In Chapeter 5, based on the resul t s in Chapter 4, a di rect and s imple method to fabr icate graphene -based metal oxide such as Co(OH) 2 nanosheet s on graphene for precluding the re -s tacking of graphene oxide reduct ion was developed. Consequent ly, graphene-based metal oxide s are thought to be the mos t promi s ing elect rode mater ial s appl icable for supercapaci tor s .
학위논문(박사)--아주대학교 일반대학원 :에너지시스템학과,2015. 2
Keywords: Supercapacitor; Electrochemical capacitor; Electrochemical analysis